The efficacy of trabectedin in treating ovarian cancer. (11th February 2017) - Teplinsky, Eleonora; Herzog, Thomas J.
ABSTRACT: Introduction : The majority of women with epithelial ovarian cancer present with advanced stage disease and there is a critical need for novel drugs and treatment strategies to improve outcomes. Trabectedin is a unique cytotoxic agent with a complex mechanism of action. It binds to guanines in the N2 position in the minor groove of DNA and its cytotoxicity involves DNA repair pathways and transcription regulation. Trabectedin's activity is also related to the drug-induced changes of the tumor microenvironment. It has been shown to improve progression-free survival in combination with pegylated liposomal doxorubicin in patients with platinum-sensitive relapsed ovarian cancer. The most common adverse events experienced with trabectedin are nausea, vomiting, fatigue, neutropenia and transaminitis. Studies of biomarkers that are predictors of trabectedin benefit are underway. Areas covered : This review covers trabectedin's mechanism of action and pharmacology, the clinical development of the drug in ovarian cancer, ongoing trials, and the use of biomarkers to predict efficacy to trabectedin. Expert opinion : Ongoing phase III trials with biomarker studies will help to elucidate the patient population that will best benefit from trabectedin and pave the way for personalized treatment decisions and potential future approval of trabectedin in the United States.